THE FORMATION OF THE FIRST MUSLIM ORGANIZATIONS IN AMERICA - Mavlonov Otabek Anvarovich (Galaxy International Interdisciplinary Research Journal, 2021)
The article elucidates the formation and development of Muslim organizations at the turn of the 20th century by using a lot of English sources. Besides, it gives important information about various Islamic organizations, their ideas and activities which are played great role in Muslims life of that period. Moreover, the author of the article focused on the role of the leaders of organizations in society and paid special attention to how their ideas conformable to the main dogmas of Islam. Particularly, the ideas of Moorish Science Temple of America and Nation of Islam have been sufficiently analyzed.